Learning Styles and Self-Efficacy as Predictors of Biology Education Students' Learning Experiences - Riska Herlena. S; Nawwir Junari (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
This study aims to analyze the influence of learning styles and self-efficacy on the learning experiences of students in the Biology Education Study Program. The background of this research is based on the importance of understanding the variation in individual characteristics in the learning process, as different learning styles can influence how students receive, process, and remember information. Meanwhile, self-efficacy serves as an internal factor that determines students' belief in their ability to effectively complete academic tasks. This research uses an associative quantitative approach with the Partial Least Square (SmartPLS) method to analyze the relationships between variables. Data was collected by distributing a Likert-scale questionnaire to Biology Education students. The research results show that all indicators have outer loading values above 0.70, thus meeting the criteria for convergent validity and construct reliability. Evaluation of the structural model (inner model) shows that learning style has a positive and significant effect on learning experience (t = 4.560; p = 0.000), and self-efficacy also has a positive and significant effect on learning experience (t = 7.375; p = 0.000). This indicates that students with a suitable learning style and high self-efficacy have a more positive and meaningful learning experience. These findings confirm the importance of the role of lecturers in designing learning strategies that are adaptive to students' learning styles and in promoting self-efficacy to improve overall student engagement and learning outcomes